Three-component N-alkenylation of azoles with alkynes and iodine(III) electrophile: synthesis of multisubstituted N-vinylazoles - Kikuchi, Jun; Nakajima, Roi; Yoshikai, Naohiko (Beilstein Journal of Organic Chemistry, 2024)
A stereoselective N-alkenylation of azoles with alkynes and iodine(III) electrophile is reported. The reaction between various azoles and internal alkynes is mediated by benziodoxole triflate as the electrophile in a trans-fashion, affording azole-bearing vinylbenziodoxoles in moderate to good yields. The tolerable azole nuclei include pyrazole, indazole, 1,2,3-triazole, benzotriazole, and tetrazole. The iodanyl group in the product can be leveraged as a versatile synthetic handle, allowing for the preparation of hitherto inaccessible types of densely functionalized N-vinylazoles.
Keywords: alkynes; azoles; cross-coupling; hypervalent iodine